Sex dictates IL-17A regulation: Inflammatory determinants in males versus a potassium-linked metabolic axis in females - David Chisompola; Emmanuel Luwaya; Martin Chakulya; Joseph M. Chalwe; Joreen P. Povia; Annet Kirabo; Sepiso K. Masenga (PLoS ONE, 2026)
Background Interleukin-17A (IL-17A) is a key Th17 cytokine involved in mucosal defense and chronic inflammation and serves as an important biomarker and therapeutic target in autoimmune, cardiovascular, and infectious diseases. Emerging evidence indicates that immune regulation may differ by sex, which may influence disease susceptibility, biomarker interpretation, and treatment response. However, few studies have examined sex-specific determinants of IL-17A. This study aimed to identify the sociodemographic, clinical, and inflammatory correlates of circulating IL-17A, with a specific focus on elucidating sex-specific determinants. Methods We conducted a cross-sectional study in a cohort of adults attending routine clinic from Livingstone University Teaching Hospital in Zambia. Plasma levels of IL-17A and a panel of inflammatory cytokines were measured. Sociodemographic, metabolic and clinical data, including HIV status and ART regimen, were collected. Sex-stratified multiple linear regression models were used to identify independent correlates of IL-17A levels with statistical significance p < 0.05. Results A total of 225 participants were recruited, comprising 71 males and 154 females, with median ages 50 (41, 59) vs. 48 (40, 58) years, respectively. Distinct sex-specific factors associated with IL-17A were identified. In males, IL-17A levels were significantly associated with a recognized inflammatory cytokine network, including positive correlations with IL-6 (Beta: 43.96, 95% CI: 30.58–57.34, p < 0.001) and IL-1β (Beta: 0.02, 95% CI: 0.02–0.03, p < 0.001), and a negative association with IFN-γ (Beta: −1.21, 95% CI: −1.65 – −0.77, p < 0.001). However, living with HIV was not a predictor of IL-17A (Beta: −1248.07, 95% CI: −2752.35–256.21, p = 0.101). Among females, none of the cytokines or HIV status predicted IL-17A; instead, plasma potassium (Beta: 9.81, 95% CI: 5.31–14.30, p < 0.001) was the only significant determinant of IL-17A. Conclusion The determinants of IL-17A are fundamentally different between males and females. These findings underscore the importance of considering biological sex as a key variable in immunology research. They suggest that IL-17A may require sex-specific interpretation as a biomarker of inflammation, particularly in HIV-associated and cardiometabolic conditions, and highlight the potential for sex-tailored therapeutic strategies targeting IL-17A-related pathways. Further studies are needed to validate these findings and explore their mechanistic and clinical implications.